2006
DOI: 10.1111/j.1365-2516.2006.01312.x
|View full text |Cite
|
Sign up to set email alerts
|

Hemophilia joint health score reliability study

Abstract: This study is the first in a series to assess the psychometric properties of the HJHS, a promising new measure of joint health in boys with haemophilia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
415
1
9

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(436 citation statements)
references
References 14 publications
4
415
1
9
Order By: Relevance
“…Veslava et al found difficulties in the domains of self-care, use of transportation and functions of the arms in haemophiliac children [12]. This difficulties at walking could be explained by numerous data in the literature that suggest ankles being most frequently affected by hemarthroses, which have a negative influence on the performance of functional tasks requiring the activity of lower limbs [13]. In our sample, we found a significant relationship between absenteeism and quality of life.…”
Section: Resultssupporting
confidence: 52%
“…Veslava et al found difficulties in the domains of self-care, use of transportation and functions of the arms in haemophiliac children [12]. This difficulties at walking could be explained by numerous data in the literature that suggest ankles being most frequently affected by hemarthroses, which have a negative influence on the performance of functional tasks requiring the activity of lower limbs [13]. In our sample, we found a significant relationship between absenteeism and quality of life.…”
Section: Resultssupporting
confidence: 52%
“…16,17 The HJHS is based on physical examination of elbows, knees, and ankles (maximum, 20-26 points per joint) and observation of gait for knees and ankles (0-4 points). The total score was calculated without adding overall global gait to the individual joint scores, resulting in a total score ranging from 0, signifying perfect joint health, to 144.…”
Section: Outcomementioning
confidence: 99%
“…The variables collected by investigators from the post-ITI period were as follows: the type of co-morbidities [cancer, cardio vascular disease, hypertension, hepatitis C, human immunodeficiency virus (HIV), renal disease, and others] as well as the date for diagnosis; their regular treatment and the date when it was resolved (if it was not currently active); the joint status of the patients by means of joint score prior to ITI and after ITI (Haemophilia Health Joint Score; HHJS [16]) and the target joints affected (shoulder, elbow, knee, ankle, hip); the amount of bleeds requiring FVIII concentrates every year after ITI until January 2015; the type of bleeding and its treatment (specifying brand, dose and regimen used of FVIII, duration of the treatment and use of bypassing agents and reason when necessary); the type of venous access complications (infections, thrombosis, port-a-cath removal, or others); the type and date of surgical procedures, their reasons and the FVIII concentrates used (brand, dose and regimen); and the number of hospitalizations in every year from ITI success until the present, specifying for each one the reason and the number of days in hospital.…”
Section: Study Proceduresmentioning
confidence: 99%